The Relationship of NADPH Oxidases and Heme Peroxidases: Fallin' in and Out - Sirokmány, Gábor; Geiszt, Miklós (Frontiers in Immunology, 2019)
Peroxidase enzymes can oxidize a multitude of substrates in diverse biological processes. According to the latest phylogenetic analysis, there are four major heme peroxidase superfamilies. In this review, we focus on certain members of the cyclooxygenase-peroxidase superfamily (also labeled as animal heme peroxidases) and their connection to specific NADPH oxidase enzymes which provide H2O2 for the one- and two-electron oxidation of various peroxidase substrates. The family of NADPH oxidases is a group of enzymes dedicated to the production of superoxide and hydrogen peroxide. There is a handful of known and important physiological functions where one of the seven known human NADPH oxidases plays an essential role. In most of these functions NADPH oxidases provide H2O2 for specific heme peroxidases and the concerted action of the two enzymes is indispensable for the accomplishment of the biological function. We discuss human and other metazoan examples of such cooperation between oxidases and peroxidases and analyze the biological importance of their functional interaction. We also review those oxidases and peroxidases where this kind of partnership has not been identified yet.